Strategi Pengembangan Perdesaan Berbasis Tanaman Industri di Kabupaten Takalar, Provinsi Sulawesi Selatan - Muhammad Anshar; Zulkifli Zulkifli (Journal of Regional and Rural Development Planning (Jurnal Perencanaan Pembangunan Wilayah dan Perdesaan), 2019)
This study aims to determine the level of development and strategies for rural development based on industrial plants. This study uses primary and secondary data in the form of village potential data, supporting facilities, population numbers, accessibility, service facilities, institutions, disasters, and infectious diseases. Rural development based on industrial plants in Takalar District is spread in most rural areas. Industry with leading commodity of sugar cane is expected to be the spearhead of village development. However, based on BPS data, there was a decrease in sugar cane productivity during 2012–2016. The result of the analysis shows that the level of rural development based on industrial plants in North Polombangkeng district was higher than that South Polombangkeng district. It can be seen from the result of the scoring analysis which shows that two villages namely Palleko village and Massamaturu village, each weights 75 and 74, are located in North Polombangkeng district. This study recommends that in balancing the level of village development based on sugarcane plants, the local government and private sector should improve infrastructure and human resources as a whole.